2022
DOI: 10.1371/journal.pone.0274137
|View full text |Cite
|
Sign up to set email alerts
|

Vortex vein congestion in the monkey eye: A possible animal model of pachychoroid

Abstract: Purpose To create vortex vein congestion in the monkey eye as a possible pachychoroid model. Methods We ligated superotemporal and inferotemporal vortex veins at the surface of the sclera in monkey eyes. Optical coherence tomography (OCT) and indocyanine green angiography (ICGA) were performed before and 2, 7, and 28 days after the vortex vein ligations to investigate changes in vortex vein morphology and alterations in choroidal blood flow. Results Before the vortex vein ligations, en face OCT and ICGA im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In this study, the areas irradiated with PDT were located near the macula. It has been hypothesized that congestion in the vortex vein plays a role in the pathogenesis of CSC and PNV [ 25 , 26 , 27 ]. Consistently, various studies have reported a vertical asymmetry in the running pattern of deep choroidal veins in PSD [ 20 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the areas irradiated with PDT were located near the macula. It has been hypothesized that congestion in the vortex vein plays a role in the pathogenesis of CSC and PNV [ 25 , 26 , 27 ]. Consistently, various studies have reported a vertical asymmetry in the running pattern of deep choroidal veins in PSD [ 20 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al performed a very interesting study creating a monkey model of vortex vein congestion by ligating two vortex veins, and they could observe pachychoroid-related findings, indicating that vortex vein congestion is involved in the pathogenesis of the pachychoroid. Nevertheless, the authors noted that the remodeling of the choroidal drainage route via intervortex venous anastomosis appeared to compensate for the vortex vein congestion created in this model [ 25 ]. In the future, it would also be interesting to observe if the cut-off value of 153 µm proposed by Shiihara et al can predict the likelihood of developing CSC.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the alteration of the RPE by co-culturing stretching HUVECs with ARPE-19 cells. Recent studies have demonstrated that the mouse and monkey choroidal congestion model can be a reliable animal model of pachychoroid [44,45], but to our knowledge there is no cellular model for this disease spectrum, and perhaps the introduction of a mechanical stretching device can provide a breakthrough to further investigate the molecular mechanism of oBRB injury under choroidal vasodilatation.…”
Section: Discussionmentioning
confidence: 99%